PENGARUH INOKULASI Ralstonia solanacearum TERHADAP PERTUMBUHAN DAN HASIL TOMAT (Solanum lycopersicum L.) YANG DISAMBUNG DENGAN TAKOKAK (Solanum torvum Swartz.) - , NISPA YUHANIS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Grafting tomato (Solanum lycopersicum L.) onto Takokak (Solanum torvum Swartz.) rootstock is an effective method to control bacterial wilt caused by Ralstonia solanacearum, a soil-borne disease. The objectives of this research were to determine the growth and yield quality of grafted tomato onto takokak and to know the resistance of tomato grafted onto takokak rootstocks to Ralstonia solanacearum. This experiment was conducted in Ngipiksari, Yogyakarta with altitude 750 m above sea level, from May 2012 to August 2012. The treatment consisted of two factors